Mao Zedong’s thought and the construction of socialist ideology - Min Zhang; Haiyong Zong; David Zeen (Trans/Form/Ação)
The 70-year practice of New China shows that our party has, permanently, attached importance and strengthened the leadership of ideological work, which is an essential factor for the Chinese nation to achieve the leap from standing, wealthy to powerful, and consolidate continuously the ruling position of the party. The successive leadership collectives of the party have explored and innovated the theory of socialist ideology in different periods of the history of China in light of the international and domestic situation, providing the CPC with a scientific theoretical basis and action guidelines for breaking through ideological barriers in its long-term rule. Mao Zedong made significant historical contributions to explore the road to new Chinese socialism, institutional design, theoretical innovation and ideological construction. The purpose of this study is to combine the basic principles of Marxism with the specific reality of China, creatively put forward the basic principles and basic directions of national ideology construction, and systematically elaborate the essential connotation, guiding ideology, primary objectives, fundamental nature and realization path of socialist ideology construction. This study shows that the first theoretical leap of the localization of Marxist ideology in China has laid a solid foundation to build a scientific and complete country and a scientific and complete national ideology system.